Resonant and Radiation Characteristics of Rectangular Microstrip Patch Antenna on Suspended-Composite Substrates - Bedra, S.; Fortaki, T. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, the resonance and radiation characteristics of rectangular microstrip patch printed on suspended and composite substrates are investigated theoretically. The analysis approach is based on the spectral-domain method of moments in conjunction with the stationary phase method. The complex resonant frequency of the microstrip antenna on suspended and composite substrates is studied with sinusoidal functions as basis functions, which show fast numerical convergence. Using a matrix representation of each layer, the far-field pattern of the suspended-composite configuration is efficiently determined by the (TM, TE) representation. The validity of the solution is tested by comparison of the computed results with experimental data. Finally, numerical results for the effects of suspended and composite substrates on the resonant frequency and half-power bandwidth are also presented.